Sources of Resistance in Accesses of Cucurbita spp. to Virus Species from the Genus Potyvirus - Barbosa, Graziela; Lima, José Albersio; Nascimento, Aline Kelly; Silva, Fabiana; Dias, Rita de Cássia (Revista Ciência Agronômica, 2017)
The present research had the objective to evaluate the phenotypic reactions of pumpkin (Cucurbita spp.) accesses to the following virus species from the genus Potyvirus: Papaya ringspot virus type watermelon (PRSV-W), Zucchini yellow mosaic virus (ZYMV) and Watermelon mosaic virus (WMV). The experiments were developed at greenhouse conditions at the Plant Virus Laboratory, Universidade Federal do Ceará, involving 28 accesses of pumpkin from the Active Cucurbit Germplasm Bank from Embrapa Semiárido. Twelve young plants from each pumpkin access were inoculated with each one of the virus species and were maintained at greenhouse for their symptom reaction evaluations. All possible virus infections or absence of infection were confirmed by plate trapped enzyme linked immunosorbent assay (PTA-ELISA) against antisera specific to PRSV-W, ZYMV and WMV. Four pumpkin accesses showed extreme resistant to WMV and seven accesses presented mild mosaic when inoculated with PRSV-W. The most severe symptoms were observed on those accesses inoculated with ZYMV and 50% of the accesses showed to be highly susceptible. On the other hand, the pumpkin accesses inoculated with WMV presented the mildest symptoms, indicating that 25% of them were moderately resistant and 39% were tolerant. The identification of source of resistance in cultivated cucurbit species is very important for production of resistant cultivars to control diseases caused by virus from the genus Potyvirus. The genotypes BGC 518, BGC 530, BGC 567 and BGC 749 that showed resistance to one or more than one virus species constitute promising source of resistance for production of virus resistant cultivars.